REPRODUCTIVE BIOLOGY OF THE FRESHWATER CLAM POKEA (Batissa violacea var. celebensis, von Marten 1897) (Bivalvia: Corbiculidae) IN THE POHARA RIVER, SOUTHEAST SULAWESI, INDONESIA - Bahtiar, Bahtiar; Anadi, La; Nurgayah, Wa; Hamzah, Muhaimin; Hernawan, Udhi Eko (SEAMEO BIOTROP, 2021)
The freshwater clam, locally known as Pokea (Batissa riolacea var. celebensis, von Martens 1897; Bivalvia: Corbulidae), is a popular and widely consumed food in Kendari, Southeast Sulawesi. Despite its popularity, basic information required for conservation management, such as reproductive biology, is lacking. Hence, this study aims to examine the reproductive biology of the clam obtained from the Pohara River, Kendari, Southeast Sulawesi Province, Indonesia. Pokea samples were collected monthly from February 2012 to January 2013. Its reproductive biology, including sex ratio, stage of gonadal maturity, gonadosomatic index (GSI), fecundity, and size at first mature gonad for each sample, was recorded. Data were analyzed using the chi-square test and linear regression in the software package SigmaPlot v.6.0. The Pokea population in the Pohara River was male-biased. The population spawns throughout the year, with the peak spawning season occurring in August–September. Mature gonads were found at small shell sizes, indicating early sexual maturity. This gonadal development in Pokea, which might have been influenced by food availability, provides very relevant baseline information for the conservation of the Pokea population in the Pohara River.